Walrus Pipes and Waving Panpipes: 3D printed instrument designs for speculative community music - Szabó, Bálint (Jazz Research Journal, 2024)
Musical instruments play a fundamental role in speculative music creations. Standing at the intersection of various fields, they embody concepts, meanings, symbols and musical consonances that are specific to each and every culture. In the present age, mass-produced Western instruments are primarily made for musical geniuses in service of virtuosity, while they all sound the consonances of a single standardized tuning system. In contrast, the 3D printed wind instrument project presented here aims to be a counterpoint to these instruments. They are simple, custom-made new instruments that work together as an ensemble, in service of communal playing. For this reason, they can be used for diverse musical purposes: they are open, nonauthoritative, and as embodiments of new meanings and uncommon consonances, they might as well be agents and representatives of speculative music worlds. This article reveals the complete design process of two 3D printed wind instrument ensembles developed throughout the project: the Walrus Pipes and the Waving Panpipes.